Līdarān-i imrūz-i Pushtūnistān - Binava, Abdul Raouf (Mudīrīyat-i ʻUmūmī-i Nasharāt-i Dākhilī, Riyāsat-i Mustaqil-i Maṭbūʻāt, 1950)
Biographical sketches of noted Pushtun political leaders of the North West Frontier Province of Pakistan.